Dietary education programs for adults with neurological diseases a scoping review protocol - Begley, Andrea; Black, Lucinda; Russell, Rebecca (Wolters Kluwer, 2020)
Objective: The objective of this review is to identify and map the evidence on the types of dietary education programs that have been implemented and evaluated in any setting for adults with neurological diseases. This review will also examine program characteristics, including program duration, length, and number of sessions, and common behavior change techniques used.